Adolescent Performance on The Awareness of Social Inference Test: TASIT. Issue 1 (30th April 2015) - McDonald, Skye; Fisher, Alana; Togher, Leanne; Tate, Robyn; Rushby, Jacqueline; English, Therese; Kelly, Michelle; Mathersul, Danielle; Froreich, Francesca; Francis, Heather
Abstract : Primary objective: Social cognition underlies social skills and can be disrupted in numerous developmental and acquired brain disorders during childhood and adolescence. Despite this, there are few tools to assess social cognition clinically in this age group. This study examined adolescent performance on The Awareness of Social Inference Test (TASIT), a valid measure of social cognition in adults. Design: Cross-sectional design examining performance on Parts 1, 2 and 3 of TASIT (and alternate forms) in Australian girls and boys with varying levels of English familiarity. Methods: 665 schoolchildren from private and government schools were administered TASIT subtests. Of these, 464 students aged 13–15 were selected to provide normative data. Scores from a further 97 provided information about the effects of lack of English familiarity. Results: The two Forms of TASIT were statistically equivalent for two of the three parts. Adolescents performed lower than adults, although the differences were not large. Some incremental effects were seen for chronological age. Gender effects were apparent on all subtests. Lack of English familiarity (i.e., English not spoken at home) reduced scores a further 6–13% relative to high English proficiency. Conclusions: TASIT appears to be suitable for adolescents. Norms are best aggregated across ages in adolescence and stratified according to gender.